DAMPAK PENGGUNAAN TEKNOLOGI WEBSITE TERHADAP PENINGKATAN KUALITAS LAYANAN PUBLIK PADA KANTOR CAMAT KADIA KOTA KENDARI - Ulfah Attamimi; Riston G. Ahmad (Journal Publicuho, 2020)
This study aims to provide an overview of the impact of technology use, namely the website at the Kadia sub-district office in the framework of improving the quality of public services. The research method used is a qualitative method with a triangulation approach, namely observation, interviews, and written or archived data. The results show that the use of website technology in Kadia sub-district is a strategic step in responding to challenges in the era of governance development and improving the quality of digital technology-based public services. Ease of information dissemination and data integration between villages and districts are advantages that should facilitate public access. This situation should be able to change the mindset of all parties, both government officials and the public, which will lead to a more effective and efficient quality of public services. However, the impact of website technology has not yet been seen on improving the quality of public services. this is because the public's knowledge is still low regarding the existence of the sub-district website and how to use it, and also the lack of socialization of the sub-district website by the sub-district government to the Kadia community.